2022
DOI: 10.14309/ajg.0000000000001773
|View full text |Cite
|
Sign up to set email alerts
|

An Objective Comparison of Vedolizumab and Ustekinumab Effectiveness in Crohn's Disease Patients' Failure to TNF-Alpha Inhibitors

Abstract: INTRODUCTION:The use of ustekinumab and vedolizumab as second-line therapies in patients with Crohn's disease (CD) in which tumour necrosis factor alpha inhibitors (TNFi) failed is still debated. The aim of this study was to compare, in a large multicenter observational retrospective cohort, the effectiveness of ustekinumab and vedolizumab as second-line therapies, as assessed by clinical and objective outcomes including endoscopy and gastrointestinal imaging.METHODS:Clinical response, remission, and steroid-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 23 publications
1
19
1
11
Order By: Relevance
“… 26 A recent multicentre-retrospective study from Italy displayed the equality of UST and VDZ in terms of achieving objective remission among patients with anti-TNF refractory CD at week 52; however, clinical remission rates differed. 27 Our study found 1-year persistence rates of 86.5% for UST and 57.9% for VDZ treatment, which are higher than the rates found by Ylisaukko-Oja et al of 46.2%–37.1% for ADA and 47.1% for UST during 12 months of treatment in a real-life setting. 28 …”
Section: Discussioncontrasting
confidence: 74%
“… 26 A recent multicentre-retrospective study from Italy displayed the equality of UST and VDZ in terms of achieving objective remission among patients with anti-TNF refractory CD at week 52; however, clinical remission rates differed. 27 Our study found 1-year persistence rates of 86.5% for UST and 57.9% for VDZ treatment, which are higher than the rates found by Ylisaukko-Oja et al of 46.2%–37.1% for ADA and 47.1% for UST during 12 months of treatment in a real-life setting. 28 …”
Section: Discussioncontrasting
confidence: 74%
“…Recent multicentre retrospective studies observed conflicting results regarding the rate of clinical remission in patients treated with ustekinumab as compared to patients treated with vedolizumab [10][11][12][13][14]. Nevertheless, in these studies, ustekinumab, and vedolizumab were not strictly used as second-line therapies, since approximately 70% of patients had previously received at least two anti-TNF agents, making direct comparison difficult.…”
Section: Introductionmentioning
confidence: 99%
“…La presente valutazione economica è stata condotta con l'obiettivo di stimare, sulla base dei risultati clinici di uno studio osservazionale, retrospettivo e multicentrico condotto in Italia (13), il costo per responder di vedolizumab e di ustekinumab nel trattamento della malattia di Crohn in fase attiva da moderata a severa nei pazienti che hanno fallito una precedente terapia con uno o più inibitori del TNF-α.…”
Section: Obiettivounclassified
“…Premessa L'analisi è stata sviluppata in ambiente Microsoft® Excel®. In linea con i timepoint adottati nello studio osservazionale (13), il costo di trattamento associato a vedolizumab e a ustekinumab è stato calcolato considerando due differenti orizzonti temporali: 26 e 52 settimane. Il costo per responder, basato sulla remissione clinica e sulla risposta clinica, di vedolizumab e di ustekinumab è stato quindi calcolato dividendo il corrispondete costo totale di trattamento a 26 o a 52 settimane per gli endpoint clinici (remissione e risposta) valutati nello studio osservazionale (13).…”
Section: Metodiunclassified